Comparative Study of Qxidative Stress, Lipid Peroxidation Marker, and Vit E Levels in Sera of Elderly Osteoarthritis Patients and Healthy Control. - Al-Elawy, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The production of reactive oxygen species in most diseases including osteoarthritis (OA) is confirmed to be the most destractive process to human cells.  To investigate the role of free radicals in patients with OA and by comparing lipid peroxidation marker maloan dialdehyde (MDA) and Vit E as one of the potent antioxidant in Sera of (OA) patients with those in healthy population.  The study includes 34 patients with knee OA diagnosed by doctors using different diagnostic parameters techniques , 18 females and 16 males and their age ranged 45 â€“ 78 years , in addition to  32 healthy control 16 males and 16 females. The result revealed a significant elevation in serum MDA sera in both patient groups ( male and female) compared to match aged healthy control groups. On the other hand a significant decrease in serum Vit E levels in both patient groups compared to control groups, was noticed.